Advances in management accounting - Epstein, Marc J.; Lee, John Y. (Elsevier JAI, 2007)
Advances in Management Accounting (AIMA) publishes well-developed articles on a variety of current topics in management accounting that are relevant to researchers in both practice and academe. As one of the premier management accounting research journals, AIMA is well poised to meet the needs of management accounting scholars. Featured in Volume 16 are articles on: Value-Creation Models For Value-Based Management: Review, Analysis, And Research Directions; Performance Standards And Managers Adoption Of Risky Projects; The Effects Of Organizational Culture On Budgetary Conflict: Integrative Ver.